Intervertebral Disc Degeneration and Ectopic Bone Formation in Apolipoprotein E Knockout Mice - Zhang, Dawei (2012)
Cardiovascular risk factors are known to be associated with intervertebral disc degeneration, but the underlying mechanism is still unclear. ApoE knockout (KO) mouse is a well-established model for arthrosclerosis. We hypothesize that ApoE may involve in maintaining disc health and ApoE KO mouse develops early disc degeneration. Discs of ApoE KO and wild-type (WT) mice were characterized with histological/immunological, biochemical, and real time RT-PCR assays. A comparison of the extracellular matrix production was also performed in disc cells. We demonstrated that ApoE was highly expressed in the endplates of WT discs and ectopic bone formed in the endplates of ApoE KO discs. Glycosaminoglycan content was decreased in both ApoE KO annulus fibrosus (AF) and nucleus pulpsous (NP) cells. Collagen levels were increased in AF and decreased in NP cells. Matrix metalloproteinases-3, 9, and 13 expression was increased which may partially explain the impaired matrix production. We also found increased collagen I, II, aggrecan and biglycan mRNA expressions in AF cells but decreased in NP cells. Apoptosis was increased in the ApoE KO NP tissue. These results suggest early disc degeneration changes in ApoE KO mice. ApoE, plus its importance to cardiovascular disease, may play a critical role in disc integrity and function.